2021
DOI: 10.3390/cells10040737
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Profile of CTEPH-Derived Endothelial Cells Is a Possible Driver of Disease Progression

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is a form of pulmonary hypertension characterized by the presence of fibrotic intraluminal thrombi and causing obliteration of the pulmonary arteries. Although both endothelial cell (EC) dysfunction and inflammation are linked to CTEPH pathogenesis, regulation of the basal inflammatory response of ECs in CTEPH is not fully understood. Therefore, in the present study, we investigated the role of the nuclear factor (NF)-κB pro-inflammatory signaling pathway i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…It has been shown that CTEPH patients presented higher plasma levels of circulating C-reactive protein (CRP) than controls 24 . Additionally, our recent results also identify a basal inflammatory profile of CTEPH-EC 25 . Both studies highlight the important role of NF-kB signaling pathway and CRP in increasing the expression of ICAM-1 and cell adhesion capacity in CTEPH-EC 26,27 .…”
Section: Cteph-ec Overexpression Of Adhesion Moleculessupporting
confidence: 62%
“…It has been shown that CTEPH patients presented higher plasma levels of circulating C-reactive protein (CRP) than controls 24 . Additionally, our recent results also identify a basal inflammatory profile of CTEPH-EC 25 . Both studies highlight the important role of NF-kB signaling pathway and CRP in increasing the expression of ICAM-1 and cell adhesion capacity in CTEPH-EC 26,27 .…”
Section: Cteph-ec Overexpression Of Adhesion Moleculessupporting
confidence: 62%
“…The activation of NFκB signaling may be associated with the pathogenesis of CTEPH. The NFκB signaling is activated in the endothelial cells within organized thrombi in patients with CTEPH [ 46 ], and the expression of inflammatory cytokines is increased [ 46 , 47 ]. The translocation of endotoxin induced by gut dysbiosis, which has recently been called “metabolic endotoxemia” [ 48 ], is associated with chronic low-grade inflammation and the development of cardiovascular diseases [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a previous study also reports that CXCLs are dysregulated in chronic thromboembolic pulmonary hypertension endothelial cells. 21 Regarding the correlation of CXCL family members with IPAH patients' clinical characteristics, one previous study shows that CXCL10 and CXCL12 are correlated with NT-proBNP, tricuspid annulus plane systolic excursion and right ventricular ejection fraction 10 ; and another study reveals that CXCL13 is associated with CRP in IPAH patients. 11 In the present study, we found that CXCL1 was positively correlated with mPAP and HsCRP, CXCL8 was positively correlated with mPAP and HsCRP, but negatively correlated with 6MWT distance, CXCL10 was positively correlated with mRAP, and CXCL12 was positively correlated with WHO-FC, mPAP, PVR and HsCRP but negatively correlated with 6MWT distance.…”
Section: Discussionmentioning
confidence: 99%